2016
DOI: 10.1016/j.tmaid.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Brucella melitensis prosthetic joint infection in a traveller returning to the UK from Thailand: Case report and review of the literature

Abstract: SummaryBackgroundBrucella spp. prosthetic joint infections are infrequently reported in the literature, particularly in returning travellers, and optimal treatment is unknown.MethodWe describe a prosthetic joint infection (PJI) caused by Brucella melitensis in a traveller returning to the UK from Thailand, which we believe to be the first detailed report of brucellosis in a traveller returning from this area. The 23 patients with Brucella-related PJI reported in the literature are summarised, together with our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…There is no consensus on how best Brucella PJI should be treated. Published case reports of Brucella -related PJI suggest that in the absence of radiological evidence of joint loosening, standard anti- Brucella antimicrobial therapy alone may be appropriate [19]. Our patient did not have evidence of joint loosening; hence, she was exclusively treated with anti- Brucella antimicrobial therapy, resulting in sustained clinical and microbiological cure without the need for revision surgery further supporting current dogma.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There is no consensus on how best Brucella PJI should be treated. Published case reports of Brucella -related PJI suggest that in the absence of radiological evidence of joint loosening, standard anti- Brucella antimicrobial therapy alone may be appropriate [19]. Our patient did not have evidence of joint loosening; hence, she was exclusively treated with anti- Brucella antimicrobial therapy, resulting in sustained clinical and microbiological cure without the need for revision surgery further supporting current dogma.…”
Section: Discussionsupporting
confidence: 75%
“…There is currently no consensus on how best Brucella PJI should be treated with regard to surgical intervention or duration of antimicrobial therapy. It is suggested based on a review of 24 cases with Brucella -related PJI that in the absence of radiological evidence of joint loosening, antimicrobial therapy alone may be appropriate [19].…”
Section: Introductionmentioning
confidence: 99%
“…Human infections can be transmitted through fluids of infected animals, for example via the consumption of unpasteurized dairy products or from aerosols of infected individuals[ 8 , 9 ]. Brucellosis can cause either an acute febrile illness, after a usual incubation period of 1-4 wk but ranging up to 6 mo, or a chronic infection, which can occur without focus and can affect any organ system[ 10 , 11 ]. The musculoskeletal system and spine are the most common sites of infection, however, and in general there is a wide spectrum of clinical manifestations that may last from several days up to several years[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incubation period is particularly prolonged for brucellosis, most cases ranging from 1 to 4 weeks but in some instances extending to as long as 6 months. 12 It has been suggested that the emergence of new, more virulent potential biological weapons make inclusion of Brucella among agents of bioterrorism to be mainly of historical significance. 6 Brucella spp.…”
Section: Characteristics As a Bioweapon And Availabilitymentioning
confidence: 99%